Behavioral spillovers from green purchases: comparing impacts on consumption and policy support - Castro Santa, Juana; Drews, Stefan; van den Bergh, Jeroen (Frontiers in Behavioral Economics, 2024)
Green labels and green advertising aim to promote products associated with less energy demands and lower carbon emissions. However, there are indications that purchasing green products may trigger negative spillover effects to subsequent pro-environmental behaviors. One policy-relevant question is whether spillovers from green purchases vary between different types of pro-environmental behaviors, notably consumption vs. policy support, and what determines any differences. Another important question is whether the price of green products affects the magnitude and direction of such spillover effects. Using an experiment among US citizens (N = 1,985), we show that spillovers from green purchases differ significantly between pro-environmental behaviors. In particular we find that spillovers are positive for green consumption and negative for climate policy support. Regarding price effects, we do not find robust evidence on their moderating role but only a tendency for cheap prices to exacerbate the direction of the spillover: negative for policy support and positive for green consumption. Finally, pro-environmental identity, previously suggested in the literature as a central moderator of spillover effects from green purchases, appears to be less determinant.